1990
DOI: 10.1111/j.1399-6576.1990.tb03146.x
|View full text |Cite
|
Sign up to set email alerts
|

The patterns of stress response in patients undergoing thyroid surgery under acupuncture anaesthesia in China

Abstract: The patterns of catecholamines (adrenaline and noradrenaline), peptide hormones (adrenocorticotropic hormone, antidiuretic hormone, beta-endorphin, growth hormone and prolactin), hydrocortisone (cortisol) and those of immunoglobulins (IgA, IgG and IgM) and total and differential leucocyte counts in the peripheral blood were investigated during and for 6 days after thyroid surgery in 20 patients (F/M: 18/2) performed under acupuncture anaesthesia, supplemented by small doses of pethidine (mean: 45.0 mg, s.d. 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Interestingly, this finding is in agreement with a previous report that acupuncture analgesia caused a decrease in neutrophil counts and increased lymphocyte counts. 4 There are several explanations for our results. Previous studies demonstrated that adrenal hormones such as corticosteroids were mainly responsible for redistribution of leucocytes between blood and other immune compartments.…”
Section: Commentmentioning
confidence: 90%
“…Interestingly, this finding is in agreement with a previous report that acupuncture analgesia caused a decrease in neutrophil counts and increased lymphocyte counts. 4 There are several explanations for our results. Previous studies demonstrated that adrenal hormones such as corticosteroids were mainly responsible for redistribution of leucocytes between blood and other immune compartments.…”
Section: Commentmentioning
confidence: 90%
“…The surgical stress response was not modified by pre-and peroperative electroacupuncture as was also the case in two other studies of electroacupuncture [11,13]. Kho and colleagues used electroacupuncture supplemented with pethidine in awake patients, but the study was performed without a control group [11].…”
Section: Discussionmentioning
confidence: 89%
“…In a previous randomized study using electroacupuncture after operation, we found a significant reduction in pethidine requirements after operation in the group given electroacupuncture [1]. In recent years there has been interest in various anaesthetic techniques which may modify the stress response to surgery [7][8][9][10][11][12][13], but only a few have examined electroacupuncture [11].…”
mentioning
confidence: 99%
“…Among the studies, prolactin level was found to be increased by acupuncture. In several other studies, prolactin is increased as a result of acupuncture treatment [39, 40]. It seems that acupuncture potentially increases prolactin level, yet more mechanism studies are needed in order to verify exact effect of acupuncture on sex hormones.…”
Section: Discussionmentioning
confidence: 99%